MECHANISM, RATES, AND CONSEQUENCES OF BASALTIC GLASS DISSOLUTION: II. AN EXPERIMENTAL STUDY OF THE DISSOLUTION RATES OF BASALTIC GLASS AS A FUNCTION OF PH AND TEMPERATURE - Gislason S.R.; Oelkers E.H. (My University, 2003)
This study is aimed at quantifying surface reaction controlled basaltic glass dissolution rates at far-from-equilibrium conditions. Towards this aim, steady-state basaltic glass dissolution rates were measured as a function of pH from 2 to 11 at temperatures from 6° to 50°C, and at near neutral conditions to 150°C. All rates were measured in open system titanium mixed flow reactors. Measured dissolution rates display a common pH variation; dissolution rates decrease dramatically with increasing pH at acid conditions, minimize at near neutral pH, and increase more slowly with increasing pH at basic conditions. The pH at which basaltic glass dissolution minimizes decreases with increasing temperature.Dissolution rates were interpreted within the context of a multioxide dissolution model. Constant temperature rates are shown to be consistent with their control by partially detached Si tetrehedra at the basaltic glass surface. Regression of far-from-equilibrium dissolution rates obtained in the present study and reported in the literature indicate that all data over the temperature and pH range 6° < T < 300°C and 1 < pH < 11 can be described within uncertainty usingr+,geo = AA exp-(EA/RT)aH+3aAl3+1/3where r+,geo signifies the geometric surface area normalized steady-state basaltic glass dissolution rate at far-from-equilibrium conditions, AA refers to a constant equal to 10-5.6 (mol of Si)/cm2/s, EA, designates a pH independent activation energy equal to 25.5 kJ/mol, R stands for the gas constant, T signifies temperature in K, and ai represents the activity of the subscripted aqueous species.